Policy Analysis of the HKPD Law: Strengthening PAD from Motor Vehicle Tax in Probolinggo City and Regency - I Nyoman Teja Kusuma; Ika Devy pramudiana; Nihayatus Sholichah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
The enactment of Law Number 1 of 2022 concerning Financial Relations between the Central and Regional Governments (HKPD Law) introduced a pivotal shift in Indonesia’s fiscal decentralization through the Motor Vehicle Tax (PKB)